2022
DOI: 10.12944/cwe.17.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon Sequestration Potential of Terrestrial Ecosystems: Trends And Soil Priming Effects

Abstract: Carbon sequestration in the terrestrial ecosystems by forest and agricultural management activities is being considered the best sustainable method to diminish the increasing concentration of atmospheric carbon dioxide (CO2). This paper presents soil carbon sequestration potential of terrestrial ecosystem and the concept of soil priming effect. According to forest survey of India, the carbon stock of Indian forests increased at the rate of 0.3% as compared to the previous assessment, i.e., from 2017 to 2019. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Soil carbon loss is another considerable factor in soil carbon sequestration. Previous studies indicated that the priming effect of exogenous carbon inputs on soil organic carbon decomposition could affect soil carbon sequestration processes [52,53]. The effect of strawincorporation-induced priming is superior to that of biochar [53].…”
Section: Rice Paddy Soil Carbon Sequestrationmentioning
confidence: 99%
“…Soil carbon loss is another considerable factor in soil carbon sequestration. Previous studies indicated that the priming effect of exogenous carbon inputs on soil organic carbon decomposition could affect soil carbon sequestration processes [52,53]. The effect of strawincorporation-induced priming is superior to that of biochar [53].…”
Section: Rice Paddy Soil Carbon Sequestrationmentioning
confidence: 99%
“…The soil organic carbon (SOC) pool is one of the most important carbon pools in terrestrial ecosystems ( Ahirwal et al., 2022 ), accounting for more than 50% of the total soil carbon ( Dinakaran et al., 2022 ). Changes in soil organic carbon not only affect the nutrient supply of soils and vegetation and the carbon balance between soils and the atmosphere but also have a large impact on the Earth’s carbon cycle and global climate change ( Lan, 2021 ; Liu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%